ChemInform Abstract: A General and Mild Catalytic α‐Alkylation of Unactivated Esters Using Alcohols. Issue 31 (August 2015) - Guo, Le; Ma, Xiaochen; Fang, Huaquan; Jia, Xiangqing; Huang, Zheng
Abstract In the presence of a NCP pincer/Ir catalyst, alcohols alkylate unactivated α‐substituted acyclic esters, lactones, and even methyl and ethyl acetates with water as a by‐product.